2009
DOI: 10.1038/ismej.2009.33
|View full text |Cite
|
Sign up to set email alerts
|

Phenazine antibiotics produced by fluorescent pseudomonads contribute to natural soil suppressiveness to Fusarium wilt

Abstract: Natural disease-suppressive soils provide an untapped resource for the discovery of novel beneficial microorganisms and traits. For most suppressive soils, however, the consortia of microorganisms and mechanisms involved in pathogen control are unknown. To date, soil suppressiveness to Fusarium wilt disease has been ascribed to carbon and iron competition between pathogenic Fusarium oxysporum and resident non-pathogenic F. oxysporum and fluorescent pseudomonads. In this study, the role of bacterial antibiosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
140
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(146 citation statements)
references
References 65 publications
1
140
0
Order By: Relevance
“…These two groups of Pseudomonas spp. are of special interest because they are wellstudied, highly effective biological control agents (19,35) and contribute to the natural suppressiveness of soils to certain soilborne diseases (22,35,36). This study was prompted by the recent report of Mavrodi et al (20), who found that Phz ϩ Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two groups of Pseudomonas spp. are of special interest because they are wellstudied, highly effective biological control agents (19,35) and contribute to the natural suppressiveness of soils to certain soilborne diseases (22,35,36). This study was prompted by the recent report of Mavrodi et al (20), who found that Phz ϩ Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…have especially important roles in the promotion of plant growth and the suppression of soilborne diseases of wheat and other crops (12,13,33). For example, isolates of Pseudomonas fluorescens that produce the broad-spectrum polyketide antibiotic 2,4-diacetylphloroglucinol (2,4-DAPG) are responsible for the natural suppression of take-all in the Pacific Northwest (35), and phenazine-producing pseudomonads contribute to the natural suppression of Fusarium wilt in soils of the Châteaurenard region of France (22).…”
mentioning
confidence: 99%
“…tritici, the take-all pathogen of wheat. In the Châteaurenard region of Dijon, France, indigenous phenazine-producing bacteria working in concert with nonpathogenic Fusarium oxysporum form the basis of natural disease suppression in these Fusarium wiltsuppressive soils (26,43). In the inland Pacific Northwest, root and crown rots caused by Fusarium culmorum, Fusarium pseudograminearum, Rhizoctonia solani AG-8, and Rhizoctonia oryzae are common soilborne diseases of dryland wheat for which commercial varieties lack resistance (6,31).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas spp. are prominent members of the suppressive soil microflora, as components of Fusarium-suppressive soils (23)(24)(25) or as strains applied to seeds, soil, or plant growth media to achieve biological control (23,(26)(27)(28)(29). Among the strains of Pseudomonas spp.…”
mentioning
confidence: 99%